ICT AND EMPLOYMENT AMONG WOMEN: A CASE STUDY OF KUDUMBASREE ICT PROJECT - M., Rashmi; Nair, Lekshmi V (European Scientific Journal, ESJ, 2014)
The Kudumbashree project from Kerala (a state in the southern part of India) has been a much discussed case for the community of practitioners, policy makers, researchers working on technology, empowerment and development. It is built around three pillars of economic, social and women’s empowerment. Its formation was the culmination of a process of community mobilization taken up by the State Government. But this article is focusing on the inclusion of gender in policies relating to information and communication technology with the aim of empowering socially excluded women as users and producers of this technology. The prominent part of this investigation is the case study of Kudumbashree ICT enterprises in the State of Kerala to understand the factors that resulted in the working of the enterprises and performance of them. Data were collected from Northern part of Kerala. Focus group discussions and interviews were the method employed to gather information.